IGF-1-Overexpressing Mesenchymal Stem/Stromal Cells Promote Immunomodulatory and Proregenerative Effects in Chronic Experimental Chagas Disease - Daniela N. Silva; Bruno S. F. Souza; Carine M. Azevedo; Juliana F. Vasconcelos; Paloma G. de Jesus; Malena S. Feitoza; Cassio S. Meira; Gisele B. Carvalho; Bruno Raphael Cavalcante; Ricardo Ribeiro-; Milena B. P. Soares (Hindawi Limited, 2018)
Mesenchymal stem/stromal cells (MSCs) have been investigated for the treatment of diseases that affect the cardiovascular system, including Chagas disease. MSCs are able to promote their beneficial actions through the secretion of proregenerative and immunomodulatory factors, including insulin-like growth factor-1 (IGF-1), which has proregenerative actions in the heart and skeletal muscle. Here, we evaluated the therapeutic potential of IGF-1-overexpressing MSCs (MSC_IGF-1) in a mouse model of chronic Chagas disease. C57BL/6 mice were infected with Colombian strain Trypanosoma cruzi and treated with MSCs, MSC_IGF-1, or vehicle (saline) six months after infection. RT-qPCR analysis confirmed the presence of transplanted cells in both the heart and skeletal muscle tissues. Transplantation of either MSCs or MSC_IGF-1 reduced the number of inflammatory cells in the heart when compared to saline controls. Moreover, treatment with MSCs or MSC_IGF-1 significantly reduced TNF-α, but only MSC treatment reduced IFN-γ production compared to the saline group. Skeletal muscle sections of both MSC- and MSC_IGF-1-treated mice showed a reduction in fibrosis compared to saline controls. Importantly, the myofiber area was reduced in T. cruzi-infected mice, and this was recovered after treatment with MSC_IGF-1. Gene expression analysis in the skeletal muscle showed a higher expression of pro- and anti-inflammatory molecules in MSC_IGF-1-treated mice compared to MSCs alone, which significantly reduced the expression of TNF-α and IL-1β. In conclusion, our results indicate the therapeutic potential of MSC_IGF-1, with combined immunomodulatory and proregenerative actions to the cardiac and skeletal muscles.